Blockade of intracellular Zn2+ signaling in the dentate gyrus erases recognition memory via impairment of maintained LTP. Issue 8 (11th February 2015) - Tamano, Haruna; Minamino, Tatsuya; Fujii, Hiroaki; Takada, Shunsuke; Nakamura, Masatoshi; Ando, Masaki; Takeda, Atsushi
ABSTRACT There is no evidence on the precise role of synaptic Zn2+ signaling on the retention and recall of recognition memory. On the basis of the findings that intracellular Zn2+ signaling in the dentate gyrus is required for object recognition, short‐term memory, the present study deals with the effect of spatiotemporally blocking Zn2+ signaling in the dentate gyrus after LTP induction and learning. Three‐day‐maintained LTP was impaired 1 day after injection of clioquinol into the dentate gyrus, which transiently reduced intracellular Zn2+ signaling in the dentate gyrus. The irreversible impairment was rescued not only by co‐injection of ZnCl2, which ameliorated the loss of Zn2+ signaling, but also by pre‐injection of Jasplakinolide, a stabilizer of F‐actin, prior to clioquinol injection. Simultaneously, 3‐day‐old space recognition memory was impaired 1 day after injection of clioquinol into the dentate gyrus, but not by pre‐injection of Jasplakinolide. Jasplakinolide also rescued both impairments of 3‐day‐maintained LTP and 3‐day‐old memory after injection of ZnAF‐2DA into the dentate gyrus, which blocked intracellular Zn2+ signaling in the dentate gyrus. The present paper indicates that the blockade and/or loss of intracellular Zn2+ signaling in the dentate gyrus coincidently impair maintained LTP and recognition memory. The mechanism maintaining LTP via intracellular Zn2+ signaling in dentate granule cells, which may be involved in the formation of F‐actin, may retain space recognition memory. © 2015 Wiley Periodicals, Inc.